If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (27 + 5y) + 12 = 18y Remove parenthesis around (27 + 5y) 27 + 5y + 12 = 18y Reorder the terms: 27 + 12 + 5y = 18y Combine like terms: 27 + 12 = 39 39 + 5y = 18y Solving 39 + 5y = 18y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-18y' to each side of the equation. 39 + 5y + -18y = 18y + -18y Combine like terms: 5y + -18y = -13y 39 + -13y = 18y + -18y Combine like terms: 18y + -18y = 0 39 + -13y = 0 Add '-39' to each side of the equation. 39 + -39 + -13y = 0 + -39 Combine like terms: 39 + -39 = 0 0 + -13y = 0 + -39 -13y = 0 + -39 Combine like terms: 0 + -39 = -39 -13y = -39 Divide each side by '-13'. y = 3 Simplifying y = 3
| 4b-4=10v | | x-4/8-x | | 4-4/8-4 | | 8.00(4.00+x)=40.00 | | 4(x-5)+8=6x-2(4+x) | | y-60=2(x-120) | | 4x^2+15x-60=0 | | */11=*/12=-11 | | -4p=-24 | | logx=.56 | | f(x)=-3x^2-2 | | 2x^4-66x^2=-64 | | 8x^4-52x^2+44=0 | | 8/12=x/14 | | 7k+9-5k-10= | | 3x-2=6x-1 | | log(2)(6x-3)=2 | | x(x+1)+(x+2)(x+3)=42 | | z=-40x-10y+1850 | | 162=-v+31 | | 182-u=47 | | 3=x/6-5 | | 3x^4-16x^2+16=0 | | cos65=15/x | | 3(x-1)=-18 | | -18y^4/-6y^2 | | 8(3x+4)=18(x+5) | | 12.8=x/4 | | 50/60=10/x | | (2x-1)(4x+4)=0 | | 2/7w=42 | | 7v=14/5 |